Integration of the multi-scale heterogeneous data for the deployment of the concept of energy efficiency in buildings within an SDI framework - Cuca, Branka; Sesana, Marta Maria; Iannaccone, Giuliana; Oreni, Daniela; Caccavelli, Dominique (My University, 2013)
The paper illustrates the potentials of geospatial information (GI) and related services that can enable structuring, access and sharing information regarding energy efficiency in buildings. This work refers on one side to European initiative that foresees a creation of macro-regions that are defined by their similarities in terms of climate, culture, construction typologies, economy, energy prices and energy policies and on the other side to the INSPIRE Directive that aims to ensure compatibility and usability Spatial Data Infrastructures (SDI) across Europe. The research here illustrated regards a geo-portal and geo-mapping tool that are able to provide new scenarios for retrieving geospatial knowledge regarding energy efficiency of European built environment.
Keywords: Energy efficiency in buildings; Geospatial web services; INSPIRE; SDI